Biosynthesis of Peptide Hydrogel–Titania Nanoparticle Composites with Antibacterial Properties - Roya Binaymotlagh; Farid Hajareh Haghighi; Enea Gino Di Domenico; Francesca Sivori; Mauro Truglio; Alessandra Del Giudice; Ilaria Fratoddi; Laura Chronopoulou; Cleofe Palocci (Gels, 2023)
The photoantibacterial properties of titania nanoparticles (TiO2NPs) are attracting much interest, but the separation of their suspension limits their application. In this study, the encapsulation of commercial TiO2NPs within self-assembling tripeptide hydrogels to form hgel-TiO2NP composites with significant photoantibacterial properties is reported. The Fmoc-Phe3 hydrogelator was synthesized via an enzymatic method. The resulting composite was characterized with DLS, ζ-potential, SAXS, FESEM-EDS and rheological measurements. Two different concentrations of TiO2NPs were used. The results showed that, by increasing the TiO2NP quantity from 5 to 10 mg, the value of the elastic modulus doubled, while the swelling ratio decreased from 63.6 to 45.5%. The antimicrobial efficacy of hgel-TiO2NPs was tested against a laboratory Staphylococcus aureus (S. aureus) strain and two methicillin-resistant S. aureus (MRSA) clinical isolates. Results highlighted a concentration-dependent superior antibacterial activity of hgel-TiO2NPs over TiO2NPs in the dark and after UV photoactivation. Notably, UV light exposure substantially increased the biocidal action of hgel-TiO2NPs compared to TiO2NPs. Surprisingly, in the absence of UV light, both composites significantly increased S. aureus growth relative to control groups. These findings support the role of hgel-TiO2NPs as promising biocidal agents in clinical and sanitation contexts. However, they also signal concerns about TiO2NP exposure influencing S. aureus virulence.